COMBINING ABILITY FOR YIELD AND YIELD CONTRIBUTING CHARACTERS IN KENAF (Hibiscus cannabinus L.) - Mostofa, M. G.; Rahman, L.; Hussain, M. M. (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Combining ability in 6 x 6 half diallel crosses were estimated for yield and yield contributing characters in kenaf (Hibiscus cannabinus L.). Combining ability analysis revealed that mean square due to general combining ability (GCA) and specific combining ability (SCA) were significant for all the characters studied suggesting the presence of both additive and non-additive gene action for the inheritance of the concerned characters. The magnitude of GCA variance was considerably higher than that of SCA variance for days to 1st flowering, fibre weight per plant and 1000-seed weight indicating the importance of additive gene action for these traits. The other characters were preponderantly controlled by non-additive gene action. Ranking of parents on GCA performance indicated that parent P6 (Acc.2731) was the best general combiner for fibre yield and yield attributes. On the other hand, parents P2 (Acc.4197) and P3 (Acc.2922) were found to be the best for seed related traits. On SCA performance, the crosses P3 x P5, P1 x P6, P3 x P6 and P4 x P5 were found to be the best for fibre related traits, while the best specific crosses for seed related traits were P2 x P3 and P2 x P4. For the development of high fibre or seed yielding kenaf varieties, either pedigree selection method or recurrent breeding is suggested depending on the genetic behavior of the trait. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16307